Sjukdomstillstånd associerade med monocytos hos svenska hundar - Ohlson, Anna (2004)
The purpuse of this retrospective study is to determine which diseases are associated with pronounced monocytosis in Swedish dogs. Records of 153 dogs with monocytosis were evaluated. The most common cause was infectious diseases (49%) of which pyometra was seen in 23% of the cases, cystitis and fever of unknown origin each in 13% and gastroenteritis in 12%. Cortison treatment was the second most common cause with 29%. A sixth of the dogs had non inflammatory diseases such as neoplasia, renal- and heartfailure. Ten per cent of the dogs had inflammatoric diseases without infection for example panostitis, artritis and gastritis. Two per cent had immunemediated hemolytic anemi. The frequency of monocytosis in different diseases is not determated. Many of the dogs with pyometra showed a cortisolpattern with neutrophilia, monocytosis and lymphopenia which suggestes that the disease supresses the immune system due to stress and cortisol release.